PENERAPAN METODE MOORA DALAM SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN DOSEN PEMBIMBING TUGAS AKHIR - Utomo, Yudo Bismo; Kurniadi, Harso; Anam, Syaiful; Rachmad, Aeri (Electro Luceat, 2024)
The Computer Engineering program at UNISKA Kediri is a study program focused on information technology. Despite being an IT-based program, the process of determining Final Project a lecture is carried out through a coordination meeting mechanism with the lecturers. In this meeting, a lecture matched based on their expertise and the topic of the Final Project proposed by each student. This discussion process requires a significant amount of time, making student services less efficient in terms of time management. To address this issue, a decision support system is needed to help the program coordinator expedite the lecture assignment process without compromising the accuracy of matching lecturer expertise to the students Final Project topics. This research uses the MOORA method (Multi-Objective Optimization on the Basis of Ratio Analysis). This method effectively conducts multi-criteria selection by considering various factors. The results of this study, based on data from 10 trials using the MOORA method, showed an accuracy of 90%, meaning that students were assigned a lecture in line with their respective areas of interest.